2015
DOI: 10.1080/17542863.2015.1041994
|View full text |Cite
|
Sign up to set email alerts
|

Language switching by bilingual therapists and its impact on the therapeutic alliance within psychological therapy with bilingual clients: a systematic review

Abstract: A systematic review was conducted to evaluate the empirical literature exploring the role of language switching in therapeutic engagement for bilingual therapists working with minority ethnic clients who share the same native language. The review identified three main themes of research focusing on: the training needs and professional development of bilingual therapists; the emotional aspects of language use; and the use of language switching and its perceived effects on the therapeutic process. The review ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition to Spanish‐speaking therapists, there is a need for bilingual and bicultural supervisors and formalized training in the delivery of mental health services in multiple languages (Castaño, Biever, González, & Anderson, ; Schwartz, Rodríguez, Santiago‐Rivera, Arredondo, & Field, ), all of which require focused efforts to prioritize bilingual and bicultural hires across multiple levels of an organization. Furthermore, as many bilingual providers cite concerns about their linguistic competence (Kapasi & Melluish, ), assessment of providers' Spanish language proficiency would help guide targeted language‐based supports needed in supervision or at the broader agency level. In particular, as our study results replicate findings from other studies in which Spanish–English bilingual providers noted difficulties in using technical terms of therapy (e.g., Verdinelli & Biever, ); it is highly likely that both consumers and bilingual providers across settings and interventions would benefit from the current study's recommendation for simplification of language used in intervention delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Spanish‐speaking therapists, there is a need for bilingual and bicultural supervisors and formalized training in the delivery of mental health services in multiple languages (Castaño, Biever, González, & Anderson, ; Schwartz, Rodríguez, Santiago‐Rivera, Arredondo, & Field, ), all of which require focused efforts to prioritize bilingual and bicultural hires across multiple levels of an organization. Furthermore, as many bilingual providers cite concerns about their linguistic competence (Kapasi & Melluish, ), assessment of providers' Spanish language proficiency would help guide targeted language‐based supports needed in supervision or at the broader agency level. In particular, as our study results replicate findings from other studies in which Spanish–English bilingual providers noted difficulties in using technical terms of therapy (e.g., Verdinelli & Biever, ); it is highly likely that both consumers and bilingual providers across settings and interventions would benefit from the current study's recommendation for simplification of language used in intervention delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, for bilinguals with relatively high L2 proficiency, practitioners should be able to speak the same languages as patients or clients. Switching between languages as needed, during psychotherapy in particular, can increase patients’ self-disclosure and emotional expression (Ramos-Sánchez, 2007; Santiago-Rivera, Altarriba, Poll, Gonzalez-Miller, & Cragun, 2009), facilitate the therapeutic alliance (Kapasi & Melluish, 2015) and be used deliberately to the benefit of the therapy (Martinovic & Altarriba, 2013). The utility of this approach may also extend from psychotherapy to communication with professionals in other sensitive professional situations (such as a legal trial or a medical procedure).…”
Section: The Potential Impact Of Bilingual Variability In the Real Worldmentioning
confidence: 99%
“…However, encountering an emotion word in the second language (L2) does not activate as many associations as in the L1 (Altarriba, 2001). Thus, it is common to observe clients engage in code switching to represent their emotions during therapy (Altarriba & Santiago-Rivera, 1994; Basnight-Brown & Altarriba, 2007; Kapasi & Melluish, 2015; Martinovic & Altarriba, 2012). Perez-Foster (1998) suggested that language code switching is deliberate, predictable, and contextually and situationally dependent.…”
Section: Training School Psychologists With a Bilingual Specializationmentioning
confidence: 99%
“…Beyond these characteristics, school psychologists might also consider assessing the student's level of acculturation and physical and mental health status in order to form an effective treatment/intervention plan (Esquivel, Oades-Sese, & Jarvis, 2010). On an ongoing basis, school psychologists might evaluate and refine treatment modalities to fit the needs and characteristics of CLD students (Basnight-Brown & Altarriba, 2007; Kapasi & Melluish, 2015).…”
Section: Training School Psychologists With a Bilingual Specializationmentioning
confidence: 99%